2019
DOI: 10.1016/j.enconman.2019.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic assessment of the horizontal geothermal heat pump systems: A comprehensive review

Abstract: Geothermal heat pump has been widely recognized as one of the promising technologies for building applications because of its high energy efficiency and low operating expense, however the high capital investment and installation costs discourage building owners to choose such a system. The horizontal geothermal heat pump system with reduced cost is a viable option that would be utilized widely, the aim of this paper is to catalogue and critique a range of effective approaches for the horizontal geothermal heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(34 citation statements)
references
References 55 publications
(92 reference statements)
1
33
0
Order By: Relevance
“…Previous studies on GSHP systems [24,25] have shown that final COP depends on system configuration and local site conditions (e.g., the BHEs setup, the climate, the ground properties, and the HP nominal power), as well as the transient operative conditions of the system's duty-cycle: the ground's undisturbed temperature, the temperature difference between the surface and the underground, and the temperature of the water leaving the heat pump and the BHEs. These temperature fluctuations lower the system COP.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on GSHP systems [24,25] have shown that final COP depends on system configuration and local site conditions (e.g., the BHEs setup, the climate, the ground properties, and the HP nominal power), as well as the transient operative conditions of the system's duty-cycle: the ground's undisturbed temperature, the temperature difference between the surface and the underground, and the temperature of the water leaving the heat pump and the BHEs. These temperature fluctuations lower the system COP.…”
Section: Introductionmentioning
confidence: 99%
“…GHPs, also known as Ground-Source Heat Pumps, typically result in less annual energy consumption when compared to conventional systems. Of the portion of energy cost associated with the HVAC system, the consumption savings is in the range of 30% to 60% over common residential HVAC systems such as an air-source heat pumps or forced air furnace with split-system air conditioning [5][6][7]. While GHPs are more energy efficient compared to air-source heat pumps and forced-air furnace systems, previous research studies identified key barriers that inhibit GHP widespread industry growth including 1) High capital cost for ground loops, 2) Low market awareness, 3) lack of knowledge in GHP benefits, and 4) Infrastructure limitations including a limited number of qualified and experienced installers [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies exist on geothermal energy, GHPs, and the installation and payback period of these systems for commercial and residential facilities [5][6][7] with many focusing on simulations of GHP systems [7,8,13] or field performance for GHPs in climates with high heating demand [14]. Limited information is known about the costs and payback period of GHPs for residential homes in hot and humid climates using field performance data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen in the summary in Table 1, the overview of the literature on indicators of refurbishment of buildings shows that most studies only consider environmental indicators, where mainly primary energy or global warming potential (GWP) are applied. In relation to the economic evaluation, although there are currently numerous studies that integrate the life-cycle cost (LCC) assessment when evaluating the impact of renewable technologies or energy systems [19][20][21], there are few studies that jointly apply the life-cycle approach to quantify and evaluate the environmental and economic impact of an energy refurbishment of a building. Table 1.…”
Section: Introductionmentioning
confidence: 99%